2022
DOI: 10.1186/s13068-022-02209-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of vitamin D3 to bioactive calcifediol and calcitriol as high-value compounds

Abstract: Biological catalysis is an important approach for the production of high-value-added compounds, especially for products with complex structures. Limited by the complex steps of chemical synthesis and low yields, the bioconversion of vitamin D3 (VD3) to calcifediol and calcitriol, which are natural steroid products with high added value and significantly higher biological activity compared to VD3, is probably the most promising strategy for calcifediol and calcitriol production, and can be used as an alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Calcitriol (1α, 25-dihydroxy vitamin D3) can be classified as a seco-steroid hormone. Vitamin D3 in humans is converted to calcitriol as an active final vitamin D3 metabolism product [17]. Research shows that the amount of vitamin D serum in MS patients influences the likelihood of getting MS and modulates disease activity.…”
Section: Resultsmentioning
confidence: 99%
“…Calcitriol (1α, 25-dihydroxy vitamin D3) can be classified as a seco-steroid hormone. Vitamin D3 in humans is converted to calcitriol as an active final vitamin D3 metabolism product [17]. Research shows that the amount of vitamin D serum in MS patients influences the likelihood of getting MS and modulates disease activity.…”
Section: Resultsmentioning
confidence: 99%
“…A further experiment was accomplished to study the effect of pH, reaction temperature, and reaction time(Tang et al 2020 ) (Wang et al 2022 ), on vitamin D 3 bioconversion activity of the chromatographic active fraction. Our Findings revealed pH 7.8 was optimum for the biotransformation process.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior research studies have applied fermenters of various sizes to study the microbial conversion of vitamin D 3 into its hydroxylated derivatives (Kang et al 2006 , 2015a , b ; Abass et al 2011a , b ; Luo et al 2016 ; Tang et al 2020 ; Wang et al 2022 ). A previous study conducted by Sasaki et al 1991 , where 300 Streptomyces isolates were screened, found two strains with a conversion productivity of about 7.0 mg/L/min.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, applied fermentation conditions (Run1) were established and these included: basal medium used for main culture and vitamin D 3 bioconversion; inoculum size of 2% v/v; agitation rate of 200 rpm; aeration rate of 1 vvm; initial pH of 7.8 (uncontrolled); temperature of 30 °C (before substrate addition) and of 28 °C (after substrate addition); addition of vitamin D 3 two days after the beginning of main culture and continual of the incubation process for additional four days. It is crucial to note that several of the conditions/factors previously described were based on a prior screening effort for optimizing vitamin D 3 bioconversion, by the research isolate, in a shake flask (Abass et al 2011b ; Wang et al 2022 ; ).…”
Section: Discussionmentioning
confidence: 99%